A Matter of Psychological Safety: Commitment and Mental Health in Turkish Immigrant Employees in Germany. (May 2016) - Ulusoy, Nazan; Mölders, Christina; Fischer, Sebastian; Bayur, Hakan; Deveci, Serol; Demiral, Yücel; Rössler, Wulf
Immigration entails the risk of feeling disconnected in the receiving society, in both everyday life and the workplace. This may affect the way immigrant employees relate to their job and their workplace. In this article, we investigate the affective commitment of Turkish immigrant employees in Germany (TG) and their subsequent work engagement, mental health, and turnover intention. Specifically, we compared TG ( n = 201) to both German employees in Germany (GG; n = 1, 406) and Turkish employees in Turkey (TT; n = 362). Our results show that the effect of immigration background on mental health, work engagement, and turnover through affective commitment depends on the level of perceived psychological safety at the workplace, specifically in terms of an open and inclusive work climate. The results suggest that psychological safety is particularly helpful in enhancing immigrant employees' positive attitudes toward the workplace. Our study provides new insights on the well-being of immigrant employees, specifically TG, and the different needs of diverse workforces. Given our findings, future studies should explore more deeply the positive influences that psychological safety has on minority groups and their workplace attitudes.